Global, regional, and national burden of intracerebral hemorrhage and attributable risk factors in youths and young adults, 1990–2021: a statistical analysis of incidence, mortality, and DALYs - Wu, Bing; Huang, Changbao; Li, Qian; Rui, Yuanyuan (Frontiers in Neurology, 2025)
BackgroundIntracerebral hemorrhage (ICH) remains a leading contributor to mortality and long-term disability worldwide. This study aims to report global trends in the incidence, mortality and disability-adjusted life years (DALYs) of ICH among youths and young adults from 1990 to 2021.MethodsThis study analyzed ICH incidence, mortality, and DALYs in youth and young adults aged 15–39 years using data from the Global Burden of Disease (GBD) database. Rates for incidence, mortality, and DALYs were calculated per 100,000 population with 95% uncertainty intervals (UIs). Data from 204 countries and territories were stratified by age, sex, and location. Temporal trends were assessed through Joinpoint regression models to compute annual percent change (APC) and log-transformed linear regression models to estimate the average annual percentage change (EAPC).ResultsGlobally, the incidence of ICH among youths and young adults in 2021 was 246938.25 (95% UI, 192258.36–303133.32), with 85038.37 deaths (95% UI, 76818.49–93855.53), and 5385247.12 DALYs (95% UI, 4884623.97–5910984.71). From 1990 to 2021, the incidence decreased by −0.4% (95% UI, −6.14 to 5.54%), mortality by −4.62% (95% UI, −14.24 to 6.74%), and DALYs by −5.08% (95% UI, −13.98 to 5.38%). The incidence rate declined from 11.31 (95% UI, 8.56, 14.27) per 100,000 individuals in 1990 to 8.30 (95% UI, 6.46, 10.19) per 100,000 individuals in 2021, an overall decrease of −26.62% (95% UI, −30.85 to −22.24). Among the five Sociodemographic Index (SDI) regions, the highest EAPCs were observed in the high SDI regions for incidence (−1.63%; 95% CI, −1.74 to −1.52), mortality (−1.79%; 95% CI, −2.01 to −1.58), and DALYs (−1.67%; 95% UI, −1.84 to −1.50). At the national level, China had the highest number of ICH cases globally in 2021, with 49364.51 cases (95% UI, 37242.00–62918.59). The main risk factors for ICH-related mortality and DALYs globally are hypertension, air pollution, and tobacco use.ConclusionThe global incidence, mortality, and DALYs of ICH among youths and young adults are generally on a declining trend. The main risk factors are hypertension, air pollution, and tobacco use. A thorough understanding of the epidemiology of ICH in youths and young adults is crucial for developing timely and effective intervention measures.